2011
DOI: 10.3727/096368910x0177
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Demonstration of Neoangiogenesis after Intra-arterial Infusion of Autologous Bone Marrow Mononuclear Cells in Diabetic Patients with Critical Limb Ischemia

Abstract: Critical limb ischemia in diabetic patients is associated with high rates of morbidity and mortality. Suboptimal responses to the available medical and surgical treatments are common in these patients, who also demonstrate limited vascular homeostasis. Neovasculogenesis induced by stem cell therapy could be a useful approach for these patients. Neovasculogenesis and clinical improvement were compared at baseline and at 3 and 12 months after autologous bone marrow-derived mononuclear cell (BMMNC) transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…Some phase I/II clinical trials also have shown that BMMNC transplantation can improve clinical outcomes of patients with middle cerebral artery occlusion (MCAO) [1114]. In fact, several independent groups have reported that BMMNC transplantation significantly reduces ischemia-induced impairment and increases vascular density and blood flow in both acute and chronic ischemic disorders, such as cardiovascular disease [15], peripheral arterial disease [16], and diabetic foot [17]. However, little research has examined the effects and possible mechanisms of BMMNC transplantation in chronic cerebral hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Some phase I/II clinical trials also have shown that BMMNC transplantation can improve clinical outcomes of patients with middle cerebral artery occlusion (MCAO) [1114]. In fact, several independent groups have reported that BMMNC transplantation significantly reduces ischemia-induced impairment and increases vascular density and blood flow in both acute and chronic ischemic disorders, such as cardiovascular disease [15], peripheral arterial disease [16], and diabetic foot [17]. However, little research has examined the effects and possible mechanisms of BMMNC transplantation in chronic cerebral hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Values are median ± interquartile endostatin (pg/ml) and median ± interquartile transcutaneous oxygen pressure (TcPO 2 ; mmHg) over time. which is currently not available or requires special techniques (19).…”
Section: Discussionmentioning
confidence: 99%
“…cells persistently increased for 1 month after the treatment only in the responders (Kajiguchi et al 2007). Similarly, neovasculogenesis in CLI diabetic patients was evaluated after infusion of unfractionated autologous BMderived mononuclear cell generating a significant increase in the vascular network in ischemic areas and promoting remarkable clinical improvement (Ruiz-Salmeron et al 2011).…”
Section: Discussionmentioning
confidence: 99%